1984
DOI: 10.1093/jac/14.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal relative inhibition factors: BAY 1–9139, bifonazole, butoconazole, isoconazole, itraconazole (R 51211), oxiconazole, Ro 14–4767/002, sulconazole, terconazole and vibunazole (BAY n-7133) compared in vitro with nine established antifungal agents

Abstract: Nine new antifungal agents were tested for their activity in vitro in terms of relative inhibition factors (RIFs) against 26 isolates of Candida species, eight isolates of Aspergillus species and six isolates of dermatophyte fungi. Eight of the new compounds were azole antifungals, the ninth was a phenylmorpholine derivative. Against Candida species, all the novel compounds gave RIFs that were of a similar order to RIFs for established imidazole compounds. Two topical antifungals, butoconazole and terconazole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…Its mode of action is not well defined, but in one study it inhibited macromolecular synthesis in the order ribonucleic acid > deoxyribonucleic acid > protein > mannan (344). RIF values for Candida species, Aspergillus species, and dermatophytes were 69, 71, and 12%, respectively (208). These values suggest that sulconazole is very active against dermatophytes, but only moderately active against Candida and Aspergillus species.…”
Section: Butoconazolementioning
confidence: 89%
See 4 more Smart Citations
“…Its mode of action is not well defined, but in one study it inhibited macromolecular synthesis in the order ribonucleic acid > deoxyribonucleic acid > protein > mannan (344). RIF values for Candida species, Aspergillus species, and dermatophytes were 69, 71, and 12%, respectively (208). These values suggest that sulconazole is very active against dermatophytes, but only moderately active against Candida and Aspergillus species.…”
Section: Butoconazolementioning
confidence: 89%
“…1,1988 demonstrated that itraconazole had potent, broad-spectrum antifungal activity. RIF values for itraconazole against isolates of Candida species, Aspergillus species, and dermatophytes all were superior to those of ketoconazole, indicating that itraconazole may be a more active compound (208). In one study, itraconazole was 100 times more potent than ketoconazole in inhibiting the growth of A. fumigatus and Aspergillus niger (184).…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
See 3 more Smart Citations